Gastric pH Comparison Between Mild and Severe Cirrhotic Portal Hypertensive Gastropathy - Asep Saepul Rohmat; Dadang Makmun; Irsan Hasan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2014)
Background: One of the causes of upper gastrointestinal bleeding in patients with liver cirrhosis is thepresence of portal hypertensive gastropathy (PHG). The prevalence of PHG in patients with liver cirrhosis isquite high but there is still inconsistency regarding the studies about gastric pH in cirrhosis patient. The aim of this study is to compare the gastric pH in mild and severe PHG due to liver cirrhosis.Method: Cross sectional method with consecutive sampling was done to all liver cirrhotic patients who came to Clinic of Gastroenterology and Hepatology in Cipto Mangunkusumo hospital from March to May 2014. Sixtytwo patients with portal hypertensive gastropathy underwent endoscopy to measure the degree of gastropathy based on Mc Cormack classification ad the mean basal gastric pH using pH-metric.Results: There are 50 (80.6%) male patients and 12 (19.4%) female patients participated in this study. Portal hypertensive gastropathy is mostly caused by hepatitis C (56.5%), hepatitis B (32.3%), non-hepatitis (8.1%) and alcohol (3.2%). The mean of gastric pH in all liver cirrhosis patients with portal hypertensive gastropathy was 2.13.The mean gastric pH in liver cirrhosis patient with mild portal hypertensive gastropathy (2.00 mEq/L) was lower than the gastric pH in severe portal hypertensive gastropathy (2.25 mEq/L) with significant differences (p0.05)Conclusion: The gastric pH in liver cirrhosis patient between mild and severe portal hypertensive gastropathy are significantly different Keywords: gastric pH, liver cirrhosis, portal hypertensive gastropathy, pH-metric